The Polarization of Ambient Noise on Mars. Issue 1 (6th January 2021) - Stutzmann, E.; Schimmel, M.; Lognonné, P.; Horleston, A.; Ceylan, S.; van Driel, M.; Stahler, S.; Banerdt, B.; Calvet, M.; Charalambous, C.; Clinton, J.; Drilleau, M.; et al.
Abstract: Seismic noise recorded at the surface of Mars has been monitored since February 2019, using the InSight seismometers. This noise can reach −200 dB. It is 500 times lower than on Earth at night and it increases of 30 dB during the day. We analyze its polarization as a function of time and frequency in the band 0.03–1 Hz. We use the degree of polarization to extract signals with stable polarization independent of their amplitude and type of polarization. We detect polarized signals at all frequencies and all times. Glitches correspond to linear polarized signals which are more abundant during the night. For signals with elliptical polarization, the ellipse is in the horizontal plane below 0.3 Hz. In the 0.3‐1Hz high frequency band (HF) and except in the evening, the ellipse is in the vertical plane and the major axis is tilted. While polarization azimuths are different in the two frequency bands, they both vary as a function of local hour and season. They are also correlated with wind direction, particularly during the daytime. We investigate possible aseismic and seismic origins of the polarized signals. Lander or tether noise can be discarded. Pressure fluctuations transported by wind may explain part of the HF polarization but not the tilt of the ellipse. This tilt can be obtained if the source is an acoustic emission coming from high altitude at critical angle. Finally, in the evening when the wind is low, the measured polarized signals may correspond to the seismic wavefield of the Mars background noise. Plain Language Summary: Seismic noise at the surface of Mars was unknown until the first measurements by the seismometers from the InSight mission in January 2019. On Earth, the microseismic noise (0.05–1 Hz) is composed dominantly of surface waves generated by the numerous sources related to ocean wave activities. On Mars, because there is no ocean, seismic noise is down to 500 times lower than on Earth reaching −200 dB in acceleration at night. In order to determine the nature of the Mars noise, we analyze its polarization with a statistical method and show that it is different to that on Earth. In the low frequency band 0.03‐0.3 Hz, we detect signals with elliptical polarization in the horizontal plane. In the high frequency band 0.3‐1Hz (HF), signals have elliptical polarization in the vertical plane. The polarization ellipse azimuth gives the direction toward the source. On Mars, these azimuths are varying as a function of local hour and season and they are correlated with wind direction during the daytime. The HF polarized signals may be explained by local effects of pressure fluctuations and/or by acoustic emission coming from high altitudes in particular conditions. It is only in the evening when the wind is low, that the measured polarized signals may correspond to propagating seismic waves that would be the Mars seismic background noise. Key Points: Seismic noise on Mars is polarized horizontally at low frequency (0.03–0.3 Hz) and vertically at high frequency (0.3–1 Hz) Polarization azimuth varies with local hour and season and follows the wind direction during the day Day polarization can partly be explained by pressure or acoustic emission and seismic wavefield may only be identified in the evening